Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPS Pada Kelas V SD Inpres Wailan - Hetty J. Tumurang (Jurnal Ilmiah Wahana Pendidikan, 2022)
The formulation of the problem in this study is: "Is the jigsaw type learning model able to improve student learning outcomes in social studies subject in class V SD Inpres Wailan. The purpose of this research is to improve student learning outcomes in social studies subject in class V SD Inpres Wailan while the benefits of this research are: (1) for students it can foster student learning motivation in the social studies learning process; (2) for teachers to improve the skills of teachers in managing the learning process; (3) for schools it can be used as reference material to improve the quality of learning in schools. The subjects of this study were teachers and fifth grade students of SD Inpres Wailan for the 2019/2020 academic year with a total of 16 students consisting of 6 female students and 10 male students. The implementation of the action follows the classroom action research procedure, namely planning, implementing the action, observing and evaluating the action, and reflecting. The technique of collecting data in this research is by observing and testing. The data in this study were analyzed by calculating the percentage of completeness of learning outcomes achieved by students classically. This classroom action research was carried out in two cycles which were carried out by applying the jigsaw type cooperative learning model to improve student learning outcomes in social studies subjects in class V SD Inpres Wailan, there was an increase. From the results of the study, in the first cycle of 16 students achieved an average score of 64.68%. Because in cycle I the KKM was not achieved in this study, it was continued in cycle II. In the implementation of cycle II there was an increase of 16 students with an average value of 91.25%. So it can be concluded that the use of the jigsaw learning model can improve student learning outcomes in social studies subjects in class V SD Inpres Wailan.